2021
DOI: 10.1093/cercor/bhab268
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Mechanisms of Somatostatin-Positive Interneurons after Traumatic Brain Injury through a Switch of α Subunits in L-Type Voltage-Gated Calcium Channels

Abstract: Unilateral traumatic brain injury (TBI) causes cortical dysfunctions spreading to the primarily undamaged hemisphere. This phenomenon, called transhemispheric diaschisis, is mediated by an imbalance of glutamatergic versus GABAergic neurotransmission. This study investigated the role of GABAergic, somatostatin-positive (SST) interneurons in the contralateral hemisphere 72 h after unilateral TBI. The brain injury was induced to the primary motor/somatosensory cortex of glutamate decarboxylase 67–green fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Cortices from the contralateral hemisphere of TBI-treated ( n = 6) and sham-treated ( n = 6) GAD67-GFP mice were isolated 24 h post-TBI ( Figure 1 A) to generate a single-cell suspension. GAD67-GFP positive interneurons and a GFP population of cells were isolated from the single-cell suspension using FACS, as described in [ 30 ]. We isolated a total of 56681 +/− 7278 GFP+ interneurons from the contralateral cortices of sham-treated animals and 46388 +/− 8901 GFP+ interneurons from TBI-treated animals ( Figure 1 B.i.).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortices from the contralateral hemisphere of TBI-treated ( n = 6) and sham-treated ( n = 6) GAD67-GFP mice were isolated 24 h post-TBI ( Figure 1 A) to generate a single-cell suspension. GAD67-GFP positive interneurons and a GFP population of cells were isolated from the single-cell suspension using FACS, as described in [ 30 ]. We isolated a total of 56681 +/− 7278 GFP+ interneurons from the contralateral cortices of sham-treated animals and 46388 +/− 8901 GFP+ interneurons from TBI-treated animals ( Figure 1 B.i.).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins of sorted cells were extracted and digested as described before in [ 30 ]. Here, the optimized single-pot solid-phase-enhanced sample preparation (SP3) protocol was used [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Post‐traumatic cell loss is the major cause of TBI‐associated neurological deficits and mortality (Guo & Ma, 2021). More recently, it was found that targeting 2α subunits of pore‐forming L‐type voltage‐gated Ca 2+ channels (VGCCs) of interneurons may help to counterbalance hyperexcitability post‐mTBI (Ihbe et al, 2021). Meanwhile, blockade of Ca 2+ ‐permeable AMPA receptors (AMPARs) function was also found critical to reduce the secondary damage following mild in vitro mechanical injury in cortical neurons by maintaining the neural circuit dynamics (Goforth et al, 2011; Spaethling et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously observed an impaired GABAergic signaling in the contralateral cortical hemisphere in adolescent mice early after traumatic brain injury (TBI), resulting in a shift of the cortical E/I ratio toward excitation ( Le Prieult et al, 2017 ). Such a trauma-induced E/I- imbalance was linked to the development of post traumatic epilepsy ( Pavlov et al, 2011 ; Le Prieult et al, 2017 ; Dulla and Pitkanen, 2021 ; Ihbe et al, 2022 ). However, we found that expression of a presynaptic voltage-gated calcium channel (CaV1.3) in somatostatin-positive interneurons counterbalances the early impaired GABAergic inhibition and hyperactivity on the cortical network after TBI ( Ihbe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a trauma-induced E/I- imbalance was linked to the development of post traumatic epilepsy ( Pavlov et al, 2011 ; Le Prieult et al, 2017 ; Dulla and Pitkanen, 2021 ; Ihbe et al, 2022 ). However, we found that expression of a presynaptic voltage-gated calcium channel (CaV1.3) in somatostatin-positive interneurons counterbalances the early impaired GABAergic inhibition and hyperactivity on the cortical network after TBI ( Ihbe et al, 2022 ). In search for compensatory mechanisms, which can rebalance the E/I ratio in the cortex, the present study made use of the GAD67-GFP knock-in mouse line (KI), a well-established mouse model to study GABAergic interneurons in living tissues ( Tamamaki et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%